Republic of Uzbekistan : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
The Welfare Improvement Strategy (WIS) of Uzbekistan has the objective of improving living standards of its people with the help of strong economic policies for all priority areas of development. The report reviews economic and social policies and assesses the living standards of its people. It also reviews the macroeconomic policies for implementing goals and priorities of the WIS in individuals and estimates the cost for the same. Studies show the need for forming a conceptual framework for the WIS implementation process as well as for monitoring and evaluating the policy strategies.